2016
DOI: 10.3926/jairm.39
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mobile marketing in airport

Abstract: Purpose: This paper seeks to analyze the effects of mobile marketing tool at airports and passengers. Design/methodology: This research approach consist of going through data files and bibliographical sources in search of information gathered by authors, institutions and organizations regarding our case study. Findings: Mobile marketing to increase passenger satisfaction and commercial income in the airports. Large airports are taking advantage of the consolidation of mobile devices in the 21st century to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…For instance, airports are implementing digital technologies in passenger stages and processes to improve passenger experience and satisfaction. Passengers have different preferences and a study showed many passengers wanted more control over their journey with additional personalized smartphone options, such as payments and services, use of biometrics and technologies at security, and digital bag tags (Florido-Benítez, 2016a; Halpern et al , 2021).…”
Section: Results Of Research In International Mobile Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, airports are implementing digital technologies in passenger stages and processes to improve passenger experience and satisfaction. Passengers have different preferences and a study showed many passengers wanted more control over their journey with additional personalized smartphone options, such as payments and services, use of biometrics and technologies at security, and digital bag tags (Florido-Benítez, 2016a; Halpern et al , 2021).…”
Section: Results Of Research In International Mobile Marketingmentioning
confidence: 99%
“…This in turn may cause users to be more inclined to perceive they are sending and receiving messages between friends, which are promotional in nature, instead of being subjected to unwelcome advertisements. Furthermore, there is a lot of information about each mobile subscriber that can be used in targeting and customizing a marketing strategy (Wais and Clemons, 2008; Florido-Benítez et al , 2014; Florido-Benítez, 2016a). For these reasons it is suggested that mobile marketing offers new opportunities for companies to achieve a greater sense of belonging of the brand with the client to generate more proximity and confidence in it (Phua, 2010; Florido-Benítez and del Alcázar, 2015; Baena, 2016; Florido-Benítez, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Brida et al (2016) show how airport information systems affect passenger perceptions of service quality at airport functional areas, while Eschen et al (2018) examine use cases for augmented and virtual reality in airport inspection and maintenance processes. Several studies investigate the impact of self-service technologies at airports ( Bogicevic et al, 2017 ; Castillo-Manzano and López-Valpuesta, 2013 ; Gures et al, 2018 ; Lee et al, 2014 ; Wittmer, 2011 ), while the use of airport digital channels such as websites, social media and mobile applications is extensively covered ( Florido-Benítez, 2016 ; Florido-Benítez et al, 2016 ; Halpern, 2012 ; Halpern and Regmi, 2013 ; Inversini, 2017 ; Martin-Domingo and Martín, 2016 ; Straker and Wrigley, 2018 ; Wattanacharoensil and Schuckert, 2015 ).…”
Section: Study Context and Hypothesesmentioning
confidence: 99%
“…Mobil uygulamaların artan öneminden dolayı, ulusal ve uluslararası literatürde, turizm (Afzaal vd., 2019;Law vd., 2018;Gupta vd., 2018;Kırlar vd., 2017;Sürücü ve Bayram, 2016;Bekar ve Özçetin, 2015), sağlık (Bidargaddi vd., 2018;McKay vd., 2018;Daly vd., 2018;Hayıt ve Ergün, 2016;Güler, 2015;Önder ve Narin, 2013;Işık ve Güler, 2010;), eğitim (Lall vd., 2019;Bano vd., 2018;Wai vd., 2018;Demir ve Akpınar, 2016;Keskin ve Kılınç, 2015;Menzi vd., 2012) gibi farklı endüstrilerde bu konu sıklıkla araştırılmıştır. Benzer şekilde havacılık sektöründe mobil uygulamalar ile ilgili farklı konular araştırılmıştır (Choi vd., 2019;Cam ve Durmaz, 2018;Suki ve Suki, 2017;Florido-Benítez, 2016;Akyol, 2014;Liu ve Law, 2013). Uluslararası literatürde havayolu işletmelerinin mobil uygulamasını sadece içerik analizi ile inceleyen sınırlı sayıda çalışmaya rastlanırken (Budd ve Vorley, 2013), ulusal literatürde konuya benzer çalışma tespit edilememiştir.…”
Section: Introductionunclassified